Current view on radiation-induced heart disease and methods of its diagnosis - R. M. Muratov; S. I. Babenko; M. N. Sorkomov (Вестник трансплантологии и искусственных органов)
In recent years, cardiologists and cardiovascular surgeons are increasingly encountering radiation-induced heart disease (RIHD) in their practice. This complication is described in literature but is poorly understood and clinically challenging. Radiation therapy (RT) is widely used in the treatment of many cancers. Despite the considerable risk of RT complications, it is used in 20–55% of cancer patients. Radiation-associated cardiotoxicity appears to be delayed, typically 10 to 30 years following treatment. Mediastinal irradiation significantly increases the risk of non-ischemic cardiomyopathy. Recent reviews estimate the prevalence of radiation-induced cardiomyopathy at more than 10%. Therefore, it is important to understand the pathophysiology of RIHD, consider risk factors associated with radiation injury, and detect the condition early.